Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1155/2007/68963
|View full text |Cite
|
Sign up to set email alerts
|

Getting Across the Plasma Membrane and Beyond: Intracellular Uses of Colloidal Semiconductor Nanocrystals

Abstract: Semiconductor nanocrystals (NCs) are increasingly being used as photoluminescen markers in biological imaging. Their brightness, large Stokes shift, and high photostability compared to organic fluorophores permit the exploration of biological phenomena at the single-molecule scale with superior temporal resolution and spatial precision. NCs have predominantly been used as extracellular markers for tagging and tracking membrane proteins. Successful internalization and intracellular labelling with NCs have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 78 publications
(109 reference statements)
2
18
0
Order By: Relevance
“…The same limitations have already been discussed for quantum dots (for review, see Reference (113). In the field of DNA and plasmid delivery, it has previously been shown that lysosomotropic agents, such as chloroquine or sucrose (114), can improve DNA delivery and subsequent exogenous gene expression.…”
Section: Facilitated Deliverysupporting
confidence: 57%
“…The same limitations have already been discussed for quantum dots (for review, see Reference (113). In the field of DNA and plasmid delivery, it has previously been shown that lysosomotropic agents, such as chloroquine or sucrose (114), can improve DNA delivery and subsequent exogenous gene expression.…”
Section: Facilitated Deliverysupporting
confidence: 57%
“…This method is non-invasive and can be used on an unlimited number of cells simultaneously. For experiments requiring QDs in the cytosol, including fluorescent labeling and potential therapeutic applications, this method can find immediate application 6,38,39. For intracellular targeting, pyrenebutyrate-mediated delivery can be coupled with developments in the functionalization of QDs to label specific cytosolic proteins 11,12,40-44.…”
mentioning
confidence: 99%
“…For many in vitro delivery applications, one would like NPs that directly reach the cytosol of the cells. 153 However, the cytosol is surrounded by the cellular membrane, which is a protein-enriched lipid double layer. Thus, there are only two principal ways to reach the cytosol.…”
Section: Nano Focusmentioning
confidence: 99%